Chimeric antigen receptor (CAR) natural killer (NK)‐cell therapy: leveraging the power of innate immunity. (20th November 2020) - Rafei, Hind; Daher, May; Rezvani, Katayoun
Summary: Chimeric antigen receptor (CAR) T cells are a rapidly emerging form of cancer treatment, and have resulted in remarkable responses in refractory lymphoid malignancies. However, their widespread clinical use is limited by toxicity related to cytokine release syndrome and neurotoxicity, the logistic complexity of their manufacturing, cost and time‐to‐treatment for autologous CAR‐T cells, and the risk of graft‐ versus ‐host disease (GvHD) associated with allogeneic CAR‐T cells. Natural killer (NK) cells have emerged as a promising source of cells for CAR‐based therapies due to their ready availability and safety profile. NK cells are part of the innate immune system, providing the first line of defence against pathogens and cancer cells. They produce cytokines and mediate cytotoxicity without the need for prior sensitisation and have the ability to interact with, and activate other immune cells. NK cells for immunotherapy can be generated from multiple sources, such as expanded autologous or allogeneic peripheral blood, umbilical cord blood, haematopoietic stem cells, induced pluripotent stem cells, as well as cell lines. Genetic engineering of NK cells to express a CAR has shown impressive preclinical results and is currently being explored in multiple clinical trials. In the present review, we discuss both the preclinical and clinical trial progress made in the field of CAR NK‐cell therapy, and the strategies to overcome the challenges encountered.